Knowledge about sources and benefits of vitamin D among high school students in Bandung, Indonesia - Gisrianti,, Reina Syafira; Dewi, Vycke Yunivita; Sahiratmadja, Edhyana (Public Health and Preventive Medicine Archive, 2021)
Background and purpose: Indonesia is a tropical country, located through the equator line which is abundantly exposed with sun. However, vitamin D deficiency among population in Indonesia is common. To increase optimal vitamin D intake, knowledge on vitamin D and the role of sun exposure early in the adolescence period is imperative. This study aims to explore the knowledge of high school students about the sources and benefits of vitamin D. Methods: This was a quantitative analytical study with a cross-sectional design using survey method, conducted in 2019. A public madrasah high school in Bandung, Indonesia, was selected using convenience sampling. A validated questionnaire was distributed to students aged 16-18 years old, containing of two parts about sources of vitamin D (10 questions) and its benefits (4 questions). Results: In total, 198 high school students participated in the study, majoring in Natural Sciences (55.6%) and Social Sciences (44.4%), of whom 76.3% were females. The proportion of students who answered correctly about vitamin D was 72.8%, whereas 61.9% had correct answers about the sources of vitamin D and 83.8% about its benefits. Female students had significantly higher score compared to males (p<0.001). Interestingly, the Natural Science students had no significant higher score compared to Social Science students (p=0.227). Conclusion: The knowledge about the source of vitamin D and its benefit among female high school students is significantly better than males, thus, special attention to male students is needed. There is a trend, although not significant, that the knowledge of students majoring in the Natural Sciences is higher compared to the Social Sciences. This study suggests the need of an integrative health education and outdoor activities, as well as a better nutrition program, focusing especially on male students and the Social Sciences class.Keywords: knowledge, vitamin D, health education, sun.